Faktor-faktor yang Memengaruhi Produksi Usahatani Edamame di Kecamatan Tamansari, Kabupaten Bogor - Silitonga, Claudia Meilin Tiara Triska; Wulandari, Eliana (Mimbar Agribisnis : Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2026)
Edamame is a horticultural commodity that has begun to be cultivated in Tamansari Subdistrict, Bogor District. However, in practice, some farmers have not optimally managed production factors such as land area, seeds, fertilizers, pesticides, and labor, which can impact the low production yields. This study aims to analyze the factors affecting edamame production. The research was conducted on 15 edamame farmers using a a quantitative approach. Data were analyzed using multiple linier regression with the assistance of SPSS software. The results of the study indicate that the seed variable had a significant effect on production.